Review: The Rothschild Canticles: Art and Mysticism in Flanders and the Rhineland circa 1300 by Jeffrey F. Hamburger - Kauffmann, M (Society for the Study of Mediaeval Languages and Literature, 1992)
Jeffrey F. Hamburger, The Rothschild Canticles: Art and Mysticism in Flanders and the Rhineland circa 1300 (New Haven, Connecticut; London: Yale University Press, 1990). xii + 336 pp.; 225 figures; 12 colour plates. ISBN 0-300-04308-2, £35.00.